Aerotropolis : the way we'll live next - Kasarda, John D.; Lindsay, Greg, 1977- (New York : Farrar, Straus and Giroux, 2011)
Outlines a panoramic view of what the authors predict will be the next phase of globalization, describing transportation-centric urban regions designed to keep workers, suppliers, and goods networked within the global marketplace.
A tale of three cities -- Just in time -- Up in the air -- Welcome home to the airport -- The aerotropolist -- Aerotropolis or bust -- The cool chain -- The Big Bangs -- The aerotropolis emirates -- The sustainable aerotropolis? -- Go West. Go out. Go -- Opening day.
Includes bibliographical references (p. [419]-443) and index.
Keywords: Airports -- Social aspects; Cities and towns; City planning; Globalization